Enantioselective Synthesis of (+)-Coerulescine by a Phase-Transfer Catalytic Allylation of Diphenylmethyl tert-Butyl α-(2-Nitrophenyl)Malonate - Lee, Sangki; Yang, Jewon; Yang, Sehun; Lee, Geumwoo; Oh, Daehyun; Ha, Min Woo; Hong, Suckchang; Park, Hyeung-geun (Frontiers in Chemistry, 2020)
A 7-step enantioselective synthetic method for preparing (S)(+)-coerulescine is reported through the use of diphenylmethyl tert-butyl α-(2-nitrophenyl)malonate (16% overall yield, >99% ee). Allylation is the key step under phase-transfer catalytic conditions (86% ee). This synthetic method can be used as a practical route for the synthesis of various derivatives of (S)(+)-coerulescine for analyzing its structure–activity relationships against its biological activities.